Um estudo sócio-discursivo do sistema pronominal dos demonstrativos no português contemporâneo - Marine, Talita de Cássia [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Partindo de uma perspectiva sócio-discursiva dos fenômenos da linguagem, este estudo apresenta uma análise descritivo-comparativa do sistema dos pronomes demonstrativos do Português do Brasil (doravante PB) e do Português de Portugal (doravante PP), a fim de caracterizarmos a configuração em que se encontram tais pronomes no uso contemporâneo da língua. Para isso, consideramos as formas demonstrativas variáveis e invariáveis (“este/isto”; “esse/isso”; “aquele/aquilo”), analisadas a partir da observação dos seguintes fatores lingüísticos: funções adjetiva e substantiva dos pronomes, matização nas referenciações e usos exofóricos e endofóricos. Cabe ressaltar que as referenciações exofóricas foram tipificados em quatro realizações dêiticas: dêixis espacial, temporal, textual e de memória; já as referenciações endofóricas foram tipificadas a partir de cinco diferentes usos: anáfora fiel, infiel, por nomeação, de memória e por elipse. É importante destacar que este estudo foi parcialmente embasado pelo modelo teórico-metodológico da sociolingüística laboviana (cf.Labov 1994; 2001; 2008) visto que, o principal objetivo desta pesquisa foi verificar se o sistema pronominal do Português se mostra ternário, tal como determina a norma culta, ou se tal, como já apontaram alguns estudos a esse respeito (cf. Nascentes, 1965; Câmara Jr. 1970, 1971, 1975; Castilho, 1978, 1993; Cid, Costa e Oliveira, 1986; Pavani, 1987; Roncarati, 2003; Marine, 2004; Pereira, 2005), mostra-se, na verdade, binário. Para a realização desta análise foi utilizado um corpus constituído por cartas de leitoras da revista brasileira Capricho, e da portuguesa Ragazza, no período de 1994 a 2005. Esse corpus nos forneceu 1449 ocorrências de pronomes demonstrativos, das quais 667 compuseram a amostra de dados do PB, e 782, do PP...

From a socio-discursive view of language phenomena, this study provides a descriptive and comparative analysis of the system of demonstrative pronouns in Brazilian Portuguese (henceforth BP) and the Portuguese of Portugal (hereafter PP). It aims to characterize the setting of the pronouns in the contemporary use of language. For this, we consider variables and invariables demonstrative forms (“este/isto”; “esse/isso”; “aquele/aquilo”), analyzed from the observation of the following linguistic factors: adjective and substantive functions of pronouns, tint in the referentiation and exophoric and endophoric uses. Exophoric referential achievements were classified in four deitic ways: spatial, temporal, textual and memory deixis; while endophoric referentiations were categorized from five different uses: faithful, unfaithful, by appointment, by the memory and ellipse anaphora. It is important to emphasize that this study was partially based on the labovian sociolinguistics methodology (see Labov 1994; 2001; 2008) since the main objective of this study was to examine whether the pronominal system of portuguese is ternary, as determined by the cultured norm, or whether, as some studies have pointed out in this regard (see Nascentes, 1965; Câmara 1970, 1971, 1975; Castilho, 1978, 1993; Cid, Costa and Oliveira, 1986; Pavani, 1987; Roncarati , 2003; Marine, 2004, Pereira, 2005), it is actually binary. For this analysis we used a corpus consisting of letters from readers of two magazines, Capricho and Ragazza, brazilian and portuguese, respectively, covering the period from 1994 to 2005. This corpus gave us 1449 occurrences of demonstrative pronouns, from which 667 composed the sample of BP, and 782, of PP. After the analysis, we found that our corpus favored a significant occurrence of the endophoric use – the exception of cataphoras – and it did not favor the exophoric use... (Complete abstract click electronic access below)
Keywords: Linguística; Língua portuguesa - Brasil; Mudanças linguisticas; Língua portuguesa - Portugal; Língua portuguesa - Pronome; Demosntrative pronouns; Linguistica variation and change; Referentiation; Brailian portuguese. eng; Portuguese of Portugal